2019
DOI: 10.3389/fchem.2019.00184
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry Assay for Quantifying Fentanyl and 22 Analogs and Metabolites in Whole Blood, Urine, and Hair

Abstract: Recently, synthetic opioid-related overdose fatalities, led by illicitly manufactured fentanyl and analogs, increased at an alarming rate, posing a global public health threat. New synthetic fentanyl analogs have been constantly emerging onto the drug marked for the last few years, to circumvent the laws and avoid analytical detection. Analytical methods need to be regularly updated to keep up with the new trends. In this study, we aimed to develop a new method for detecting the newest fentanyl analogs with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 36 publications
1
79
1
Order By: Relevance
“…From the present case study, it seems that Salamone's findings would probably reflect occasional exposure to fentanyl and furanylfentanyl rather than low rate of incorporation into the keratin matrix because the concentrations in the second hair analysis clearly demonstrated high rate of incorporation of the two compounds into the hair. Moreover, Busardò et al [27] have also reported high concentrations of fentanyl in hair (mean 2670 ± 184 pg/mg, n=2), confirming our findings.…”
Section: Validation Results For the Analytical Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…From the present case study, it seems that Salamone's findings would probably reflect occasional exposure to fentanyl and furanylfentanyl rather than low rate of incorporation into the keratin matrix because the concentrations in the second hair analysis clearly demonstrated high rate of incorporation of the two compounds into the hair. Moreover, Busardò et al [27] have also reported high concentrations of fentanyl in hair (mean 2670 ± 184 pg/mg, n=2), confirming our findings.…”
Section: Validation Results For the Analytical Methodssupporting
confidence: 92%
“…Overall, at least 28 deaths were reported across Europe and the United States during 2017, largely in a home environment, which showed that in at least some of these cases the poisoning was so severe that the poisoned persons were unable to call for help [36]. Methoxyacetyl norfentanyl, a metabolite of methoxyacetylfentanyl was not screened in our method, but as reported by Busardò et al [27], this metabolite is not a suitable biomarker of methoxyacetylfentanyl consumption, and was not detected when methoxyacetylfentanyl was taken, whether in blood or urine.…”
Section: Validation Results For the Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only a few targeted screening methods for NSOs identification and quantification in hair have been published so far 19–22 . In this study, we describe the development and validation of a targeted LC–MS/MS assay for the detection and quantification of 16 fentanyl analogs and metabolites, and one non‐fentanyl derivative (U‐47700) in hair, and demonstrate its suitability in routine practice by the screening of 137 authentic hair samples collected from high‐risk populations in Paris and its suburbs.…”
Section: Introductionmentioning
confidence: 96%